THE IMPACT OF PRENUPTIAL AGREEMENTS ON PROPERTY OWNERSHIP LEGAL STATUS OF INTER-MARRIAGES - Khanza, Yuga Narazua; Okubo, Haruki; Mirantama, Ninda (Sriwijaya Crimen and Legal Studies, 2023)
Intermarriage is becoming more popular due to globalization's impact on increasing human interaction across national borders. As intermarriage becomes more prevalent, it gives rise to complex issues, with one notable concern being the legal entanglements arising from the ownership of assets or property by each partner during the marriage. This study focuses on the diverse issues associated with intermarriage in Indonesia, where legal consequences vary according to the nationality of each spouse. Notably, property ownership status, particularly concerning land and immovable assets, poses significant challenges due to the restrictions imposed on foreign citizens. In addressing these challenges, the article explores prenuptial agreements' potential role in navigating property ownership issues between spouses. The paper acknowledges the methodological and theoretical complexities inherent in establishing a clear link between intermarriage and prenuptial agreements, given the diverse ways these concepts are theorized and operationalized. Qualitative research methods and literature reviews are employed to gather insights, drawing on various research publications and news items that shed light on the legal implications of intermarriages involving individuals with different citizenships. The study's findings underscore the significance of prenuptial agreements in providing a legal framework for delineating the rights and obligations of spouses in matters of property ownership. By examining the property ownership status in intermarriages, this research contributes to a better understanding of the legal landscape surrounding such unions. The article concludes with a discussion of the implications of prenuptial agreements in shaping property ownership dynamics within the context of intermarriage.